PEMANFAATAN EKSTRAK BATANG TANAMAN PISANG (Musa paradisiacal) SEBAGAI OBAT ANTIACNE DALAM SEDIAAN GEL ANTIACNE - F.X. Sulistiyanto Wibowo; Erna Prasetyaningrum (Universitas Wahid Hasyim Semarang, 2015)
ABSTRACTBacterial resistance to antibiotics is a problem that is being faced in both the developing and developed countries. Therefore it takes an effort to diminish these problems by the discovery of new drugs derived from natural ingredients, the banana plant (Musa paradisiaca).The purpose of this study to determine the bactericidal effect of the banana plant stem in antiacne gel dosage forms. The benefity of this study is providing basic information about the benefits of stem extract of banana plants, especially in the health field that is as antiacne.This study found the class of compounds contained in extracts of banana plants include steroids, triterpenoids, alkaloids, plavonoid, tannins and saponins. Results of this study, the pH 4 FI, FII 4, FIII4; Fi viscosity of 204 cps, 216 cps FII, FIII 239 cps; lekatFI power, FII, FIII less than a minute; dispersive power FI> 7cm / 100 grams, FII and FIII> 7cm / 150 grams. Microbiological test FI: 1,337, FII: 1.474 and FIII: 1,529.Keywords: banana stems, antibacterial, antiacne gel, S.aureus